Psychometric Properties of Bully, Fighting, and Victimization Scales Among Clinically Referred Youth. Issue 10 (26th November 2018) - Ahmed, Annisa; Moore, Tyler M.; Lewis, Jason; Butler, Laura; Benton, Tami D; Boyd, Rhonda C
ABSTRACT: Bullying involvement is a multidimensional issue and a significant concern for school-aged youth. However, research on bullying involvement within clinical samples is limited. The present study examines the psychometric properties of the University of Illinois Bully, Fighting, and Victimization Scales among children and adolescents presenting for mood symptoms at a behavioral health outpatient clinic. Patients (n = 165) with an age range of 8–18 years were included in this investigation. Item frequencies, internal consistency, and construct validity were examined while confirmatory and exploratory factor analyses were conducted. Results showed that the scales were low to moderately correlated with each other. Internal consistencies were acceptable for the Bully (α = .70), Fighting (α = .84), and Victimization (α = .88) Scales. Exploratory factor analysis revealed clean three-factor solutions with items loading on their intended factors and with few cross-loadings. Fit of the confirmatory factor analysis was good when items were treated as ordinal and two items were allowed to cross-load on more than one factor. The University of Illinois Bully, Fighting, and Victimization Scales show utility for use with clinically referred youth.